2002
DOI: 10.1034/j.1600-0412.2002.810612.x
|View full text |Cite
|
Sign up to set email alerts
|

The term breech presentation. A retrospective study with regard to the planned mode of delivery

Abstract: Elective CS for breech presentation will significantly decrease the risks for the fetus in comparison with planned VD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
4
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 25 publications
(26 reference statements)
3
4
0
2
Order By: Relevance
“…The proportion of infants with low Apgar scores was greater in the group of planned vaginal breech delivery than after elective CS or after vaginal delivery with cephalic presentation. This finding is in agreement with earlier reports (3,9,10) and suggests a greater tendency for acute fetal distress during delivery, probably caused by more frequent umbilical cord stretching or compression before delivery in breech cases.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The proportion of infants with low Apgar scores was greater in the group of planned vaginal breech delivery than after elective CS or after vaginal delivery with cephalic presentation. This finding is in agreement with earlier reports (3,9,10) and suggests a greater tendency for acute fetal distress during delivery, probably caused by more frequent umbilical cord stretching or compression before delivery in breech cases.…”
Section: Discussionsupporting
confidence: 94%
“…After the TBT, two Scandinavian studies reported an increased incidence for neurological morbidity after planned vaginal breech delivery if compared to elective CS or normal cephalic presentation. The authors came to the same conclusion as the TBT and recommended a planned CS for all breech cases (9,10).…”
mentioning
confidence: 85%
“…Common features of the French/Belgium, the Finnish, the Austrian and our study, include strict selection criteria for whom should be offered vaginal delivery, close fetal monitoring and the presence of skilled obstetricians. The relatively high frequency (15%) of undiagnosed breech presentation at birth in our study has also been found in other studies (17-21%) supporting the importance of being able to handle an unexpected breech delivery vaginally [23-25]. …”
Section: Discussionsupporting
confidence: 90%
“…Oleh karena itu pada bayi presentasi bokong cukup bulan lebih banyak dipiilih bedah kaisar elektif. 5,6 Uji retrospektif yang dilakukan selama 7 tahun oleh Kayem dkk, 1 menyimpulkan bahwa pada bayi presentasi bokong tidak terdapat perbedaan morbiditas dan mortalitas yang bermakna antara kelahiran bayi pervaginam dibandingkan dengan bedah kaisar. Demikian pula Uotila dkk, 7-9 dan beberapa peneliti lain mendapatkan hasil perinatal yang baik pada persalinan sungsang pervaginam.…”
Section: Hasilunclassified
“…5,6 Berdasarkan usia gestasi dan berat lahir maka nilai Apgar <7 lebih sering terjadi pada kelompok bayi prematur dan berat lahir rendah, tanpa mempertimbangkan cara kelahiran. Prematuritas dan berat lahir rendah berperan penting dalam terjadinya asfiksia.…”
Section: Kesimpulan Dan Saranunclassified